Safety Pharmacology Study of Medicines Used for Febrile Syndrome Management in Children - K. L. Kryshen; A. E. Moshkov; M. N. Demyanovskiy; M. A. Kovaleva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Summary. Safety pharmacology studies of paediatric medicines are an important stage in the life cycle of drugs.The purpose of the study was to analyse and compare the safety pharmacology profiles of the recommended paediatric dosage regimens of a fixed ibuprofen (IBU)/paracetamol (PAR) combination and of IBU and PAR monopreparations following repeated oral administration of these products to juvenile rats. Material and methods: safety pharmacology was assessed in both male and female outbred juvenile rats. Two dose levels were used in the study-the highest treatment dose (HTD) equivalent for juvenile rats, and the three-times-equivalent therapeutic dose (3 HTD). The animals were given the fixed IBU/PAR combination in the form of suspension from dispersible tablets (100 mg IBU + 120 mg PAR), IBU in the form of oral suspension (100 mg/5 mL), and PAR in the form of oral suspension (120 mg/5 mL). Statistical processing was performed using Statistica 10.0 software. Results: unlike monopreparations, the fixed IBU/PAR combination did not have clinically significant hepatotoxic or nephrotoxic effects when administered to juvenile rats. Administration of IBU alone resulted in an increase in blood urea nitrogen concentration in female rats (HTD) and male rats (3 HTD), and a small amount of leucocytes in the urine of female rats. Administration of PAR resulted in an increase in the amount of red blood cells in the urine of male rats. Administration of the monopreparations at the HTD dose led to a decrease in the locomotor activity of the animals. No significant effect on the cardiovascular or respiratory systems was observed for any of the products.Conclusions: the safety pharmacology profile of the fixed IBU/PAR combination after repeated oral administration to juvenile rats did not differ much from those of IBU and PAR used alone, and in some cases was even better.